Airborne Demonstration of Multichannel SAR Imaging - Gebert, Nicolas; De Almeida, Felipe Queiroz; Krieger, Gerhard (IEEE Geoscience and Remote Sensing Letters, 2011)
Multichannel synthetic aperture radar (SAR) makes it possible to obtain high-resolution wide-swath imagery, thus overcoming an inherent limitation of conventional SAR. To cope with a nonuniformly sampled data array in azimuth caused by variations of the pulse repetition frequency, these systems require appropriate coherent processing such as the multichannel reconstruction algorithm. This letter presents the applicability of this algorithm to airborne measured multichannel X-band data. In this context, impact and performance of different channel-balancing methods are investigated. Furthermore, the analytic prediction of residual azimuth ambiguities is verified in the measured data by means of a point target analysis. © 2011 IEEE.
DLR Import::2019-04-02
Keywords: Airborne data; F-SAR; high-resolution wide-swath synthetic aperture radar; multichannel azimuth processing